2013
DOI: 10.1242/dev.083865
|View full text |Cite
|
Sign up to set email alerts
|

Notch1 functions as a negative regulator of lymphatic endothelial cell differentiation in the venous endothelium

Abstract: In development, lymphatic endothelial cells originate within veins and differentiate via a process requiring Prox1. Notch signaling regulates cell-fate decisions, and expression studies suggested that Jag1/Notch1 signaling functions in veins during lymphatic endothelial specification. Using an inducible lymphatic endothelial Prox1CreERT2 driver, Notch signaling was suppressed by deleting Notch1 or expressing dominant-negative Mastermind-like in Prox1+ endothelial cells. Either loss of Notch1 or reduced Notch s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
104
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(116 citation statements)
references
References 46 publications
(91 reference statements)
12
104
0
Order By: Relevance
“…Notch signaling regulates many aspects of BEC biology, including arteriovenous differentiation and angiogenesis (36,37). The role of Notch during sprouting lymphangiogenesis remains controversial: Notch signaling blockade was shown to both inhibit and promote lymphatic growth, suggesting a highly context-dependent role of this pathway (38)(39)(40)(41). In BECs, the Notch ligand DLL4 is highly expressed in tip cells, where it regulates sprouting through the induction of Notch signaling in stalk cells (42)(43)(44)(45)(46); however, the expression pattern of DLL4 in the small intestine vasculature has not to our knowledge been studied.…”
Section: Resultsmentioning
confidence: 99%
“…Notch signaling regulates many aspects of BEC biology, including arteriovenous differentiation and angiogenesis (36,37). The role of Notch during sprouting lymphangiogenesis remains controversial: Notch signaling blockade was shown to both inhibit and promote lymphatic growth, suggesting a highly context-dependent role of this pathway (38)(39)(40)(41). In BECs, the Notch ligand DLL4 is highly expressed in tip cells, where it regulates sprouting through the induction of Notch signaling in stalk cells (42)(43)(44)(45)(46); however, the expression pattern of DLL4 in the small intestine vasculature has not to our knowledge been studied.…”
Section: Resultsmentioning
confidence: 99%
“…The jagged 1/Notch1 pathway was shown to act as negative regulator of lymphangiogenesis in mice by repressing the Coup-TFII/Prox1 signaling axis (Murtomaki et al, 2013), thereby inducing maintenance of a venous cell identity. In addition, in vitro studies demonstrate that Notch overactivation represses the expression of lymphatic markers via downstream effectors of Notch signaling (Kang et al, 2010).…”
Section: Transcriptional Control Of Lymphatic Cell Fate Specificationmentioning
confidence: 99%
“…HdLECs isolated from human neonatal foreskins (Columbia IRBAAAB-1700) were maintained in EGM-2MV BulletKit (Lonza) with VEGFC (10 ng/ml, RnD) (Murtomaki et al, 2013). HdLECs were infected with adenovirus expressing constitutively active Notch1 (N1IC) or Notch4 (N4int3), or Hey1, Hey2, lacZ or GFP (Shawber et al, 2007;Tung et al, 2009).…”
Section: Constructs and Cell Culturementioning
confidence: 99%
“…Notch regulates lymphatic sprouting events in physiological and pathological settings (Niessen et al, 2011;Zheng et al, 2011). We have shown that Notch functions in embryonic venous endothelium to restrict the number of venous ECs that adopt the lymphatic fate (Murtomaki et al, 2013).…”
Section: Introductionmentioning
confidence: 99%